Efektifitas Inovasi Pelayanan Pengurusan Paspor Secara Kolektif (Eazy Passport) pada Masa Pandemi Covid-19 di Kantor Imigrasi Kelas I TPI Padang - Sonia Junita; Afriva Khaidir (Jurnal Teori dan Riset Administrasi Publik, 2022)
This research is motivated by the lack of interest in collective services (eazy passport) during the pandemic at the TPI Padang class I immigration office, the public still lacks understanding in using the collective passport service procedure (eazy passport) and the implementation of collective passport services (eazy passport) is still ineffective. ) at the immigration office class I TPI Padang. Therefore, the Class I immigration office of TPI Padang is expected to be more aggressive in conducting socialization regarding collective service innovations (eazy passport) during the pandemic and can also evaluate the procedure for the number of passport applicants with a minimum provision of 50 applicants which is considered too burdensome for agencies wishing to participate. in this service. The purpose of this study was to describe the effectiveness of the innovation of collective passport management services (eazy passport) during the COVID-19 pandemic at the Class I immigration office of TPI Padang. This research is processed using a qualitative approach with a descriptive method. This research was conducted at the immigration office class I TPI Padang. Data collection techniques were carried out through interviews, observation, and documentation. Based on the results of research and discussion, it was found that the effectiveness of the innovation of collective passport management services (eazy passport) during the covid-19 pandemic at the immigration office class I TPI Padang can be said to have not been implemented effectively because there are still few institutions that participate in using the collective passport service (eazy passport). passport) for a period of one year implementing this service at the Immigration Office class I TPI Padang.